ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH ARITMETIKA SOSIAL DI SMPN 18 MODEL SPMI PALU - Ayu Munira; Sutji Rochaminah; Bakri M. (Universitas Tadulako, 2021)
This study aims to describe students' mathematical representation skills in solving Social Arithmetic problems at SMPN 18 SPMI Palu Model. This research is a qualitative research with subjects NL, WD, and ID. The results showed that subjects (NL) with high abilities and (ID) with moderate abilities had similar mathematical representation abilities, namely good and good enough in solving problems on Social Arithmetic material and fulfilling all indicators of mathematical representation ability, namely visual representation, verbal representation and representation. symbolic. Meanwhile, subjects (ID) with low ability have poor mathematical representation skills in solving problems on Social Arithmetic material and do not meet all indicators of mathematical representation ability, namely visual representation, verbal representation and symbolic representation.